Yu-Gi-Oh! GX. Vol. 9, Beyond the struggle-- - Kageyama, Naoyuki (Shonen Jump manga., 2012)
"The possessed Principal Mackenzie makes his final bid to crush the students of Duel Academy and seize Chazz and Jaden's Spirit Cards! Jaden will need all his dueling skill as he battles his way through to the final Duel, fighting for his friends, his mentor Koyo Hibiki, and the fate of Duel Academy itself!" -- from publisher's web site.